Branding Marketing Melalui Internalisasi Budaya Sebagai Upaya Pengembangan Sustainability Tourism di Wisata Sumber Maron - Ratna Fajarwati Meditama; Ary Kusuma Purwady; Rachmad Imam Tarecha; Anisa Hudi Widaningrum; Novia Ratnasari; Amalia Agung Septarina; Indah Martha Fitriani; Muhammad Imron (I-Com: Indonesian Community Journal, 2024)
Sumber Maron located in Malang Regency, has great potential to be developed as a sustainable local culture-based tourist destination. However, the challenge of managing and promoting this potential effectively remains an obstacle for destination managers and local communities. To overcome this, branding marketing outreach activities through cultural internalization were carried out as part of efforts to develop sustainable tourism in Sumber Maron. The results of this activity show an increase in participants' awareness and ability to integrate cultural values ​​into tourism marketing strategies. The participants were also able to formulate a branding concept that is more focused on the sustainability and authenticity of local culture, which is expected to increase the competitiveness of Sumber Maron as a leading tourist destination. This activity makes a significant contribution to strengthening sustainable tourism in Sumber Maron, as well as empowering local communities to manage and promote their tourism potential independently and responsibly